FORMATIVE ASSESSMENT: THE KEY TO MOTIVATION AND SUCCESSFUL LEARNING (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article deals with the relevance of the introduction of formative assessment in the educational process as a way to improve students' motivation and performance. The impact of the updated assessment system on individualization of learning activities and formation of critical thinking in students is analyzed. The results of the study emphasize the importance of taking into account the personal achievements of students to create a supportive educational environment.